PENGEMBANGAN LKPD BERBASIS PROBLEM BASED LEARNING PADA PELAJARAN BIOLOGI MATERI SISTEM PERNAPASAN DI MADRASAH ALIYAH - Parapat, Ernita Jahara; Ulfa, Syarifah Widya; Dwi JayantI, Ummi Nur Afinni (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
The aim of developing student worksheets based on Problem-Based Learning are appropriate, effective, and practical respiratory system material to help participants learn in the learning process. This research is a research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation). The research instrument uses interview sheets, questionnaires, validation sheets, and tests. Data analysis techniques are carried out quantitatively and qualitativelyThe purpose of quantitative data analysis is to determine the degree of feasibility, practicality and effectiveness. Meanwhile, quantitative analysis consists of finding comments, criticisms, suggestions and observations. The result of the study shows that the worksheets of the students based on the problem-based study developed by 82% (media expert) are correct and feasible. 100% (Subject Matter Expert) and 100% (Language Expert), Student Worksheets are also graded on Teacher Answer Sheet achievement with 90.91% and Student Answer with 93%. Student worksheets are also considered effective if a total N-Gain of 0.76 is achieved in the high category. Based on the result above, it can be concluded that the student worksheet is Problem-Based Learning that has been developed is declared feasible, practical, and effectively used in the learning process. The developed student worksheets can improve the learning activities of students and teachers can use student worksheets as teaching materials in the learning process. Kata kunci: Lembar Kerja Peserta Didik, Problem Based Learning, Sistem Pernapasan